The Moderating Role Of Independent Commissioner In The Relationship Between Tax Aggressiveness And Firm Value - Shidqi, Farhan; Darmawan, M. Irvan; Ramadhan, Muhamad Ilham; Firmansyah, Amrie (Educoretax, 2024)
Tax aggressiveness poses agency problems within companies. This is due to the differing interests between investors and management. Independent commissioners play a crucial role in ensuring that the decisions made by management align with investor interests. The research aims to a further investigation of the moderation role of independent commissioners on tax aggressiveness actions undertaken by management from the investors' perspective. The sample consisted of 185 companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange (BEI) during the years 2018-2022. This research utilizes a quantitative method with a multiple linear regression model approach. The findings of the study indicate that tax aggressiveness has a positive effect on firm value, signaling that tax planning activities by management are still perceived as not overly aggressive and are in line with investor interests. The study's findings also show that independent commissioners are unable to moderate the negative impact of tax aggressiveness on firm value. This indicates that the role of independent commissioners has not yet been able to prevent tax aggressiveness actions that are not aligned with investor interests. This research fills a gap in previous studies that did not consider the role of independent commissioners as supervisors of management in decision-making. The implications of this research are that companies need to enhance the quality of independent commissioners through strengthening the selection process and there is a need for strengthened tax regulations that encourage companies to pay taxes.